Specific IgG subclass antibody pattern toAspergillus fumigatus in patients with cystic fibrosis with allergic bronchopulmonary aspergillosis (ABPA). Issue 1 (1st January 1999) - Skov, M; Pressler, T; Jensen, H E; Høiby, N; Koch, C
Abstract : BACKGROUND: IgG and IgG subclass antibodies to Aspergillus fumigatus (A fumigatus) were measured in a large population of patients with cystic fibrosis to elucidate a putative antibody pattern specific for allergic bronchopulmonary aspergillosis (ABPA). METHODS: An ELISA technique using water soluble somatic hyphal (WSSH) A fumigatus antigens and subclass specific monoclonal antibodies was used for cross sectional quantification of IgG and IgG1–4 subclass antibody levels in the serum of 238 patients with cystic fibrosis and 107 healthy controls. RESULTS: In patients with cystic fibrosis persistently colonised with A fumigatus the subclass antibody levels were significantly increased compared with patients with cystic fibrosis never or rarely colonised (p<0.001). The group of patients persistently colonised with A fumigatus with ABPA (+Af+ABPA) had significantly increased levels of IgG antibodies to A fumigatus (Af-IgG) (median 69 ELISA units (EU) versus 31) and of subclasses Af-IgG1 (91 versus 27), Af-IgG2 (143 versus 56), and Af-IgG4 antibodies (72 versus 20), but not of IgG3 (17 versus 15), compared with the colonised patients without ABPA (+Af–ABPA). Patients with cystic fibrosis with no or only rare isolates of A fumigatus without ABPA (–Af–ABPA) also had significantly increased subclass antibody levels (Af-IgG1 9 versus 3, Af-IgG2 28 versus 5, Af-IgG4 16 versus 4; p<0.001) compared with healthy controls. Low, although detectable, levels of antibodies were demonstrated in healthy controls. ABPA seemed to occur independently of Pseudomonas aeruginosa infection. Using diagnostic cut off levels for ABPA, sensitivity and specificity were calculated. The highest specificity was found for IgG4 (88%); sensitivity was between 65% and 73%. The positive predictive values (PPV) were moderate, whereas the negative predictive values (NPV) were high (96% in all subclasses except IgG3 with 94%). PPV increased to 50% if IgG1 as well as IgG2 and IgG4 were included. CONCLUSIONS: In a large number of unselected patients with cystic fibrosis significantly increased levels of Af-specific antibodies belonging to total IgG and all four subclasses were found in all groups of patients compared with healthy controls. In patients persistently colonised with A fumigatus these levels were significantly higher than in non-colonised patients, and the significantly highest levels (with the exception of IgG3 ) were found in patients with ABPA. Using a sensitive ELISA technique, measurements of IgG and IgG subclass antibodies to A fumigatus might be of importance in the management of ABPA, especially as a screening test to exclude the presence of ABPA; other tests are needed to confirm the diagnosis.